Manuel Castells and Informationalism - Costa, C. M.; Quintanilha, T. L.; Mendonça, S. (Management, organizations and contemporary social theory, 2019)
Understanding how the social appropriation of information and communication technologies came to define the contemporary period is critical for researchers and practitioners of innovation, business and management. This paper explores how the work of Manuel Castells as a social theorist provides the intellectual tools and the encompassing lenses to enable the study and navigate the process of structural transformation in which our lives have been engulfed from the 1970s onwards. Castells’ procedure of considering technology, social usages and structural history leads him to a key conceptual result: the introduction of the “Network Society” concept. His ideas have most notably been applied to the field of communications studies, which he analyses through the prism of power. However, these insights are not containable in one single discipline as the implications of informationalism stretch in a variety of directions, making other dimensions of society amenable to the network perspective. Organisational studies are one topic in which this line of enquiry may fruitfully be pursued.